2013
DOI: 10.1039/c3sc22306j
|View full text |Cite
|
Sign up to set email alerts
|

“Push-no-pull” porphyrins for second harmonic generation imaging

Abstract: The established approach to design a molecule with strong second-order nonlinear optical (NLO) activity is to connect an electron-donor to an electron-acceptor via a p-conjugated bridge, to generate push-pull system. Surprisingly, we have found that dyes with large first hyperpolarizabilities, and which exhibit strong second harmonic generation (SHG), can be created just by attaching an electron-donor to a porphyrin. The free-base porphyrin core is sufficiently electron-deficient that the hyperpolarizability d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Organic materials have a broad range of applications such as high-resolution fluorescence microscopy [1][2][3][4][5][6][7], second harmonic generation (SHG) microscopy [8][9][10][11][12], dye sensitized and polymer solar cells [13][14][15][16][17], solid state dye/organic lasers [18][19][20], and organic light emitting diodes [21,22], to name a few. Photostability of organic compounds and polymers is often a requirement for applications incorporating light-matter interaction [2-4, 6, 8, 18-20, 23-30].…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials have a broad range of applications such as high-resolution fluorescence microscopy [1][2][3][4][5][6][7], second harmonic generation (SHG) microscopy [8][9][10][11][12], dye sensitized and polymer solar cells [13][14][15][16][17], solid state dye/organic lasers [18][19][20], and organic light emitting diodes [21,22], to name a few. Photostability of organic compounds and polymers is often a requirement for applications incorporating light-matter interaction [2-4, 6, 8, 18-20, 23-30].…”
Section: Introductionmentioning
confidence: 99%
“…JW-1 and IG-1 dyes were functionalized with isophthalic derivatives substituted with four HEG and twelve TEG groups, respectively, instead of the pyridinium-based electron-acceptor group as the hydrophilic moiety. The dyes do not require pyridinium-based electron-acceptor groups because it has been previously shown that an acceptor group does not substantially contribute toward the nonlinear optical properties of free-base donor-acceptor-substituted porphyrin dyes ( Annoni et al., 2005 , Lopez-Duarte et al., 2013 , Morotti et al., 2006 ). Multiple HEG and TEG groups were used to enhance the aqueous solubility and amphiphilicity of dyes for efficient plasma membrane localization.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, there has been only one report of an SHG-only dye (named as Ap3 ) that is suitable for multimodal imaging ( Nuriya et al., 2016 ). Although Ap3 possesses negligible fluorescence quantum yield and does not emit any fluorescence even in the far-red region unlike AK-1 , it generates similar or less SHG signals even than FM4-64 in contrast to the donor-acceptor porphyrin-based AK-1 , which gives almost three times more SHG signal than FM4-64 ( Khadria et al., 2017 , Lopez-Duarte et al., 2013 , Nuriya et al., 2016 , Reeve et al., 2009 ). Although AK-1 gives a fluorescence signal in the far-red to NIR regions even with a low fluorescence quantum yield, it does not give any fluorescence in the green and red regions, where most of the commercial cell markers emit ( Bestvater et al., 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Porphyrins functionalized on meso-positions by quaternary pyridinium units, also referred to as cationic porphyrins are a large class of compounds with interesting physicochemical properties [22][23][24][25][26][27]. They serve as photosensitizers in photodynamic therapy (PDT) in treatment of cancer [28] and show affinity for serum albumin [29], important in drug delivery.…”
Section: Introductionmentioning
confidence: 99%